Studies on the Mango-Ecosystem in Papua New Guinea with special reference to the ecology of Deanolis sublimbalis Snellen (Lepidoptera, Pyralidae) and to the biological control of Ceroplastes rubens Maskell (Homoptera, Coccidae) - Krull, Stefan Magnus Eugen; Justus Liebig University Giessen (My University, 2004)
Studies on epigeal and arboreal and predatory arthropods in two mango orchards in the Central Province of Papua New Guinea Predatory arthropods were studied by the beating method and pitfall trapping in twomango orchards in the Central Province of Papua New Guinea (PNG). Both orchardswere not sprayed with synthetic insecticides during or before the study period.Formicidae were the most numerous group within the epigeal and the arboreal arthropods(2772 and 2269 ind., respectively). The weaver ant, Oecophylla smaragdina, was themost abundant species within the arboreal arthropods. Pheidole spp. was most frequent inpitfall traps. Spiders were the second most numerous group (524 and 619 ind.,respectively). Lycosidae were predominant in pitfall traps and Salticidae in net catcheswith the beating method on the trees. In the barber traps, Carabidae and Staphylinidaewere only present in low numbers (47 ind.). Coccinellidae were the most numerousfamily within the arboreal predatory beetles (89 ind.). Telsimia sp. accounted for 63 % ofthe ladybird beetles. Crickets were frequently collected in pitfall traps (187 ind.). A survey on the occurrence and importance of mango pests in the Central Province of Papua New Guinea A survey was conducted at four sites in the Central Province of Papua New Guinea todetermine the abundance and importance of nine insect pests in mango. The pests, exceptfruit flies which were monitored by fallen fruits, were monitored three times during 2002according to their occurrence within the mango season. Out of these pests, the whitemango scale Aulacaspis tubercularis, (Homopt., Diaspididae), the mango leafminerAcrocerops spp. (Lep., Gracillariidae), the leafhoppers ,Idioscopus clypealis and ,I.niveosparsus (Homopt., Cicadellidae), the soft scales Saissetia sp. and Parasaissetia sp.(Homopt., Coccidae) and the fruit fly Bactrocera frauenfeldi (Dip., Tephritidae) provedto be serious pests. Appropriate control measures, in particular biological and culturalmethods, are proposed. Infestation levels with fruit piercing moths Othreis fullonia, O.materna, Eudocima salaminia (Lep., Noctuidae), aphids Toxoptera odinae (Homopt.,Aphididae), blossom feeders Cosmostola sp., Gymnoscelis sp., Nanaguna breviuscula(Lepidoptera) and planthoppers Colgaroides acuminata, Colgar sp., Scolypopa sp.(Homopt., Flatidae, Ricaniidae) were lower. Appropriate control measures arerecommended but not immediately required. On the biological control of Ceroplastes rubens (Homopt., Coccidae) with the introduced parasitoid Anicetus beneficus (Hym., Encyrtidae) A study was conducted in three provinces of Papua New Guinea to determine damage bythe pink wax scale Ceroplastes rubens and to identify endemic parasitoids andparasitization levels in order to evaluate the necessity and possibility of a classicalbiological control with an introduced parasitoid. Infestation levels with the pink waxscale variied 3.82 % and 6.40 %. The parasitization levels variied between 1.19 % and3.05 %. Out of the nine endemic parasitoids identified, Aprostocetus sp. (Hym.,Eulophidae) was the most frequent one. The pink wax scale parasitoid Anicetus beneficus(Hym., Encyrtidae) was imported from Australia and released at four sites in the CentralProvince in March/April 2002. The establishment was controlled at two sites six resp.twelve months after release. Parasitization levels increased significantly (from 3.05 % to5.45 % at Laloki and from 2.04 % to 22.15 % at Tahira). At both sites, A. beneficus wasthe most frequent parasitoid. The parasitization process at the Laloki site was disturbedby the ant Tapinoma sp. Studies on the biology of Deanolis sublimbalis (Lep., Pyralidae) and its natural enemies A study was conducted at four sites in the Central Province of Papua New Guinea todetermine infestation levels and biological behaviour of the red banded mango caterpillarDeanolis sublimbalis (RBMC). Eggs and larvae were collected to identify naturalenemies and to develop potential control strategies. Infestation levels of mango fruitsvariied between 3.36 % and 23.18 %. The eggs are mainly found at the peduncle coveredwith dried sepals. Pupation takes place inside the bark of the mango tree. No other plantsthan Mangifera spp. were confirmed as hosts in laboratory and field studies. The pestgoes into diapause during mango off-season. No egg or larval parasitoids were recorded.Control measures like sticky bands are an appropriate method to prevent pupation in thebark. A spraying scheme needs to be developed for commercial producers. It is furtherrecommended to search for potential natural enemies in the centre of origin of M. indica.
Untersuchungen zum Mango-Ökosytem in Papua Neu Guinea unter besonderer Berücksichtigung der Biologie von Deanolis sublimbalis Snellen (Lepidoptera, Pyralidae) und der biologischen Bekämpfung von Ceroplastes rubens Maskell (Homoptera, Coccidae)
Keywords: ddc:570